BANK AKTIVLARI VA PASSIVLARI O’RTASIDAGI MUNOSABATNING BANK DAROMADLIGIGA TA’SIRI - Ibroximov Ilxomjon Shavkatjon o’g’li, Qadamova Muxayyo Javoxir qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This study examines the impact of the relationship between bank assets and liabilities on bank profitability, highlighting the critical role of effective asset-liability management in financial performance. Banks generate income primarily through interest earned on assets such as loans and investments, while liabilities, including deposits and borrowings, represent the cost of funds. The balance between these two elements determines net interest income (NII) and net interest margin (NIM), both key indicators of profitability. Factors such as interest rate spreads, asset quality, maturity mismatches, and liquidity management significantly influence the bank‘s profitability. A well-managed asset-liability mix enhances income stability and reduces risks associated with interest rate fluctuations and liquidity constraints. Conversely, poor management can lead to reduced margins, increased risk exposure, and potential financial instability. Understanding and optimizing the interplay between assets and liabilities is essential for banks to maximize profitability, manage risks, and sustain long-term growth in a competitive and regulated environment. From this point of view, in this article, I tried to reveal the importance of the net interest margin in increasing the profitability of the bank, as well as the state of management of bank assets and liabilities in the banking system of the Republic of Uzbekistan and its effect on the efficiency of the banking system.